Analysis Of Anticancer Activity And Its Molecular Interaction Mechanism Of Withanone, An Active Ingredient Of Withania Somnifera Using Molecular Docking: Life Sciences-Withania Somnifera for Anticancer activity - Ben Raj; S. R. Madhan Shankar (International Journal of Life Science and Pharma Research, 2022)
Withania somnifera is an annual evergreen shrub from the Solanaceae family, commonly known as Indian ginseng or Ashwagandha. The plant is mainly found in Asia and Africa regions. In the traditional Indian medicinal system ayurveda, Withania somnifera is used as a rejuvenator and sold in many countries as a dietary supplement. Withanolides are the major phytochemical constituent group found in the Withania somnifera, among which withaferin A and withanone, are considered to be major withanolides, which believed to be involved in majority of biological activity of Withania somnifera. Various studies including both in vitro and in vivo have reported regarding the anticancer potential of Withania somnifera. Along with the anticancer activity of W.somnifera, the anticancer efficacy of one of its major ingredients Withaferin A is also studied previously. This study aimed to analyse the anticancer potential of another major Withanolide present in W. Somnifera, Withanone. The study used Molecular Docking method to find the molecular binding affinity of Withanone towards various cancer proteins. The four major cancer proteins were B-cell lymphoma- extra large (Bcl-xL), Cellular FLICE (c-FLIP), Glutathione Reductase (GR) and Glutathione S- Transferases (GST). The protein structure obtained from the protein data bank and the structure of the molecule obtained from pubchem were modified and prepared for Docking studies with the help of MGL Tools. The protein ligand interaction study was conducted using the software, Autodock vina. The already known anticancer standard, 5-FluoroUracil is used as standard for comparison. Output obtained from the study is visualised using molecular visualiser tool, Pymol. Like the Withaferin A, Withanone also exhibited promising anticancer activity while studied using molecular docking methods.